The Aurat March (2018-2022) in the Context of Gendered-Islamophobia: A Case of Muslim Women’s Identity in Pakistan - Syeda Mehmoona Khushbakht (Journal of Islamic Thought and Civilization, 2022)
The role and identity of Muslim women around the world is one of the crucial issues in the current era. Women rights’ activists and other contributors seek to highlight women issues through their work and marches. The present research explores that how these marches are contributing hugely in presenting the image of women in any country to the world. The researcher addresses the cultural and religious differences in terms of gendered Islamophobia and the impact of Aurat March while constructing or contesting the women identity in Pakistani society. Through an analysis of Aurat March, researcher highlights the ways in which the biased representation of Muslim women lives can be either limiting or encouraging. The impact of these events can be reason of rise in negative attitudes and scattered stereotypes, or it might initiate peaceful dialogues and affective measures. The research also analyzes that how a minor negligence can be an additional certificate in the world of Islamophobia and an increase in international narratives against Muslims, Islam, and Pakistani society. The research paper seeks to argue how Aurat March, influenced by secular modern trends transmit Islamophobic stereotypes towards Islam: Muslim women, in general, and Pakistan in specific context. The paper will conclude by analyzing the important insights to counter the gendered Islamophobia in the lives of Muslim women while limiting themselves into gender, culture, and religion.